Efektivitas Ice Breaking dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Pendidikan Pancasila di SMP Negeri 6 Banjarmasin - Yulia Fitri; Muhammad Elmy (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
Often, students are not fully present in class learning, which comes from students’ attention and learning motivation, as they are not fully ready to attend class. Therefore, it is interesting to test the effectiveness of applying icebreaking in Pancasila Education learning for students of SMP Negeri 6 Banjarmasin to foster student interest in fully following the lesson. The effectiveness was tested quantitatively using a quasi-experimental research type and a nonequivalent control group design. All students of grade VII at SMP Negeri 6 Banjarmasin became the population in this study. The Control class sample was selected from VII B and the Experimental class from VII A. The data were analyzed with the help of SPSS version 27 to conduct prerequisite tests and non-parametric hypothesis tests. The results showed that ice breaking applied in the Pancasila Education subject class was able and effective in arousing student enthusiasm to follow the class fully. The experimental class that used ice breaking showed a higher increase in student enthusiasm when compared to the control class that underwent learning without ice breaking. Therefore, the use of ice breaking provides a much more effective and impactful way to increase motivation compared to conventional learning without it.